2011
DOI: 10.1294/jes.22.17
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Prevalence of Brucellosis in Horse Stables in Two Northern States of Nigeria

Abstract: Despite the endemicity of brucellosis in Nigeria, reports on equine brucellosis are rare. The Rose Bengal Plate Test (RBPT) was used to determine the serologic prevalence of Brucella abortus antibodies amongst 75 horses from three stables in two States of northern Nigeria. The highest prevalence (22.7%) was recorded in stable C located in Plateau State and the lowest (6.7%) was found in stable B in Kaduna State. The overall prevalence determined was 14.7%. There is need for the inclusion of horses in brucellos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 8 publications
(9 reference statements)
1
20
2
Order By: Relevance
“…The overall prevalence of 07.8% by RBPT and 00.0% by SAT in this study is comparable to the findings of other workers carried out in horses in Nigeria; 14.7% (Ehizibolo et al, 2011) and 4.8% (Bale and Kwanashie, 1984). It is however higher than 5.5% (Sadiq et al, 2013) in other equines (donkey) in Borno and Yobe States by both RBPT and SAT and 4.2% in lowlands of central Oromiya, Ethiopia (Jegerfa et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The overall prevalence of 07.8% by RBPT and 00.0% by SAT in this study is comparable to the findings of other workers carried out in horses in Nigeria; 14.7% (Ehizibolo et al, 2011) and 4.8% (Bale and Kwanashie, 1984). It is however higher than 5.5% (Sadiq et al, 2013) in other equines (donkey) in Borno and Yobe States by both RBPT and SAT and 4.2% in lowlands of central Oromiya, Ethiopia (Jegerfa et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Ehizibolo et al (2011) also reported that all the mares in their study were negative when screened with RBPT. The higher prevalence of the Brucella antibodies in the male in this study could be as a result of the low population of female horses sampled There are controversial reports regarding the prevalence of brucellosis in relation to the sex of animals, as some of the research workers reported significantly higher prevalence in males than females (MacMillan and Cockrem, 1986).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The overall prevalence of brucellosis among donkeys in Borno and Yobe states in north eastern Nigeria in this study was 5.5%. The result of the present study is lower than the 14.7% reported for horses by Ehizibolo et al (2011). The difference in prevalence could be attributed to differences in sample size and equine species; 75 horses compared with 600 donkeys in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Knowledge of diseases of donkeys is scanty, and is often extrapolated from knowledge of diseases of horses (Pearson et al, 1997). Serological surveys of Brucella antibodies in horses in Northern Nigeria indicate a prevalence of 4.8% (Bale & Kwanashie, 1984), 14.7% (Ehizibolo et al, 2011). Ocholi et al (2004a) have reported the isolation of Brucella abortus biotype 1 from a foal.…”
Section: Introductionmentioning
confidence: 99%